Frequency components of radargrams in analyses of shallow soil cavities - S.M, Daniliev; N.A, Danilieva (International Journal of Engineering and Technology, 2018)
The urgency of the issue being studied is determined by widespread large-scale implementation of ground penetrating radar (GPR) method within the study practice of technical state of various engineering-geological sites over a long operational period. Such buildings and structures as dams, architectural landmarks, residential and industrial buildings, temples and churches, roadways and takeoff runways may be referred to main engineering and geological sites which have been studied via ground penetrating radar method. Cracks of different length, orientation and opening, as well as cavities of various localization, being distinguished by filling material, are the main types of irregularities in the above-mentioned sites, which were being formed in the process of prolonged or improper operation. However, due to vastness of the irregularities being studied and the impossibility to include all the types of possible defects into this article, we have settled on the cavities which are the most commonly encountered in the course of practice only. This article considers the approach to analysis of the electromagnetic wave field frequency characteristics being applied during conducting ground penetrating radar studies of irregularities in the structure of engineering-geological sites on the basis of the results of electromagnetic wave fields mathematical simulation, and of the results obtained in experimental studies at real engineering-geological sites as well. There has been proposed a method based of inverse Fourier transformation for studying spectrum shift in georadargrams. The georadargram is a set of registered signals, which is obtained during even movement of the georadar along the survey line. Due to that, this article is aimed at attraction of analysis of wave electromagnetic field attributes in addition to standard methods of ground penetrating radar (GPR) data processing and interpretation, which allows to extend significantly prospect capabilities of GPR method by obtaining extra data on heterogeneous zones parameters at engineering and geological sites, and, thus, proceed from qualitative notions on technical condition of studied object to quantitative ones. Â Â